(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The study of foreign languages in modern society is becoming an inseparable component of the professional training of specialists of various profiles, and the successful solution of professional growth issues and the expansion of contacts with foreign partners largely depend on the quality of their language training. The success of training largely depends on the methodology of a foreign language teacher, on his ability to use various modern methods in the context of solving specific educational problems.